Informatização da rede Municipal de Ensino de Belo Horizonte: uma análise do seu impacto sobre o trabalho docente - Jacqueline de Castro Laranjo (2008)
The dissertation described the impact of informatics and communication technologies on the teachers work process of the Primary Education and the Education for Young and Adult People on Belo Horizonte public schools. The objective was to analyze the technology impact on the teachers work, focusing the nowadays economical context, turned to the exploration of the intellectual work component, characterizing the assumed new form of the exploration based on relative surplus value. So we tried to find how to identify a way as teachers could incorporate these technologies on their classes considering aspects as time and work intensification. We will try to verify how these aspects could mobilize individually or together for the appropriation of these instruments available at the school and also analyzing the conditions of continuous formation and the teachers professional growth. The methodological strategy was used on this case study with free observation, documental analyzes and semi-structure interviews. These methods were chosen because they are more interesting on the observation of the new technologies insertion on the teachers view. The use of this qualitative approach was justified for the process analyses on the teachers work as a complex study on the social nature where the social context understanding became an important element for this research. There were selected three primary education of Belo Horizonte public school with computers rooms and focusing a low social economical context, but the schools should make difference with their politics and pedagogical practices for the students development. During the observation a documental research on the pedagogical politics projects and the curriculum school classes for research data referring to the technology implantation. There were interviewed six teachers, two of them because of projects development related with the technology use and between the teachers we chose one teacher that had technology formation offered by GPLI/SMED and other teacher that didnt have. The results showed computers implementation and its use on the analyzed schools. Although, the computers rooms were incipient and inadequate. The technologies impact on the teachers work showed a contradiction on the interviewed teachers speech. Even showing significant changes on the pedagogical practice because of the technology use, we couldnt verify a significant change, the teachers kept using expositive classes using the computer. We could observe that the technologies intensified the teachers work that used the equipment on their free time. This could be an abuse of the intellectual teachers work. We could observe that the teachers formation were continuous or at work but they were still insufficient, with short time and poor. Its necessary to prepare the teachers for the new changing perspective of the computers use on the education. The results showed the need to argue about the schools structure and organization on a deep way and collective understanding to show ways for flexible times and spaces to incorporate the technology.